Effect of continuous renal replacement therapy on serum levels of inflammatory cytokines/interleukin-17 in severe acute pancreatitis - Diana Iosif; Adrian Paul Suceveanu; Marius Prazaru; Iulia Cindea; Viorel Gherghina; Anca Mihaela Pantea Stoian; Laura Mazilu; Dragos Serban; Alina Nicoara; Andra Iulia Suceveanu (Journal of Mind and Medical Sciences)
Despite continuous investigations in the diagnosis and treatment of severe acute pancreatitis (SAP), this disease still remains a critical condition with a mortality rate of up to 35%. The pathophysiology of SAP involves an important inflammatory reaction of the pancreas (mediated by inflammatory cytokines and immune system activation), causing severe local tissue damage as well as important systemic imbalances. IL-17 is an inflammatory mediator that have a pivotal role in SAP evolution, generating multiple interactions between inflammatory cytokines and significantly influencing the immune system response. Consequently, continuous renal replacement therapy/CRRT was added to the conventional therapy, leading to improved treatment results. This review aims to evaluate the involvement of Interleukin 17 in the diagnosis, pathogenesis and evolution of SAP, as well as the role of CRRT in reducing elevated serum levels of IL-17. As a conclusion, CRRT is a promising method to eliminate cytokine mediators from the blood, thus leading to a reduction of both pancreatic/peripancreatic tissue damage and systemic imbalances in severe acute pancreatitis, being strongly correlated with better therapeutic outcomes.